Behavioral comorbidities of early-life seizures: Insights from developmental studies in rats - Grígelová, Andrea; Mikulecká, Anna; Kubová, Hana (Epilepsy & behavior, 2025)
Childhood epilepsy is frequently associated with neurobehavioral comorbidities such as depression, anxiety, cognitive impairments, and social dysfunction, as revealed by both clinical and experimental studies. Despite extensive neurophysiological research, behavioral studies in developing animals remain limited and underreported. Here, we review the behavioral impact of early-life seizures (ELSs) in commonly used rat models in developmental studies. We outline suitable tests and provide guidance on how traditional tests should be adapted and interpreted in this context. Finally, we examine factors influencing behavioral analysis in developmental studies, exploring confounding variables and offering strategies to minimize their impact.
Keywords: Animals; Development; Epilepsy; Seizures; Animal models; duševní poruchy; komorbidita; lidé; chování zvířat; Comorbidity; Early life seizures; modely nemocí na zvířatech; Rat; Disease Models, Animal; krysa rodu Rattus; Behavior, Animal; Mental Disorders; zvířata; Rats; Behavior; záchvaty; Humans